Lifetime Measurement of the 14keV State in the Nuclear Decay of 5°Co(EC) to 5"Fe - C. GARCLA, MERLITA; L. RESERVA, ROSARIO; M. BACALA, Ph.D., ANGELINA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The beta decay of 57Co to 57Fe undergoes two modes. In this research the mode which leads to two excited states for 57Fe is taken into consideration. The de-excitation of the second excited state to the first excited state gives off a 122 keV gamma ray photon while the de-excitation of the first excited state to the ground state gives off a l4 keV gamma ray photon. In this decay mode the emission of the gamma photons are in cascade and are then considered to be coincident. Lifetime measurement uses the principle of the method of coincidence. The detection of these two energies are made possible by the assembly of two different sizes of scintillation detectors. The scintillators used are Sodium lodide(Nal) doped with Thallium. To detect the 122 keV gamma photon, a 2" in photon diameter by 2" thick scintillator is being used and to detect the 14 keV gamma photon, a l “in diameter by .25 " thick scintillator is being used. Using the Nuclear Instrumentation Modules (NIM) such as amplifiers, gate generators, delays etc. and the Computer Automated Measurements and Control(CAMAC) modules such as the Analog to Digital Converters (ADC) and the Time to Digital Converters(TDC) with their proper calibrations, and using a macro in fortran, the energy spectra of the particles of interest incident on these detectors can be viewed in the monitor of a personal computer and the time between the detection of these two energies can also be determined. The ADC spectra are analyzed using the RO0T data analysis system for histogramming and fitting. In the acquisition of the ADC data, unwanted counts found in the ADCs are removed. Once the TDC data is at hand, it is converted totime by multiplying the data with the slope of the TDC calibration curve. In taking the lifetime data to be analyzed, TDC data is selected which corresponds to the selected ADC I data(122 keV particles) and the selected ADC 2 data (14 keV particles). The mean lifetime of the 14 keV state of 57Fe is determined by plotting the distribution of the time between the detection of the gamma ray of these two energies. Using the ROOT suite of programs, an exponential fit is made to the TDC time distribution and the mean lifetime of the first excited state of 57Fe is then calculated.